6(3x-6)=10x

Simple and best practice solution for 6(3x-6)=10x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(3x-6)=10x equation:


Simplifying
6(3x + -6) = 10x

Reorder the terms:
6(-6 + 3x) = 10x
(-6 * 6 + 3x * 6) = 10x
(-36 + 18x) = 10x

Solving
-36 + 18x = 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
-36 + 18x + -10x = 10x + -10x

Combine like terms: 18x + -10x = 8x
-36 + 8x = 10x + -10x

Combine like terms: 10x + -10x = 0
-36 + 8x = 0

Add '36' to each side of the equation.
-36 + 36 + 8x = 0 + 36

Combine like terms: -36 + 36 = 0
0 + 8x = 0 + 36
8x = 0 + 36

Combine like terms: 0 + 36 = 36
8x = 36

Divide each side by '8'.
x = 4.5

Simplifying
x = 4.5

See similar equations:

| a+3ab+6+7a-2ab-1=0 | | 75+5x=10x+100 | | 9b-7b+6=-4b+78-3b | | 11x-160=56-7x | | 10+58=6x+2 | | 2x^4+3x-50=0 | | 5a+4b-5(7a-9b)= | | 26w+20=956 | | X-2x=125 | | (1+y)x^2-3yx+(1-y)=0 | | 2.50(m+15.00)=412.5 | | 84=2x-4+2x+4 | | 75=4529 | | -1-10r^2=-881 | | 3.4=y+2.1 | | -3x^2+8x-6=0 | | -8p-8=-14-7p | | -2x+(-21)=23 | | -1-10r^2=881 | | 84=4x^2-8+8-16 | | 929=97+13r | | 31/2(6x-21/2)+51/3=-62/3(-3x+16/5)+122/3 | | -70=-2(n+5)+7(4-6n) | | 21m-9= | | 15(b+17)=555 | | 7(f+37)=693 | | -147=-5x-4(-5x+18) | | 10x-1=35+x | | 200=2z | | -23(u-946)=-322 | | 2m^2+9=41 | | x+(x-40)=92 |

Equations solver categories